2000
DOI: 10.1017/s0017089500010120
|View full text |Cite
|
Sign up to set email alerts
|

Reflective subcategories

Abstract: Given a full subcategory [Fscr ] of a category [Ascr ], the existence of left [Fscr ]-approximations (or [Fscr ]-preenvelopes) completing diagrams in a unique way is equivalent to the fact that [Fscr ] is reflective in [Ascr ], in the classical terminology of category theory.In the first part of the paper we establish, for a rather general [Ascr ], the relationship between reflectivity and covariant finiteness of [Fscr ] in [Ascr ], and generalize Freyd's adjoint functor theorem (for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…In the previous Corollary 3.7 we showed that the class F of locally torsion-free quasi-coherent sheaves is the right part of a torsion theory in Qcoh(X). One immediate consecuence of this is that each M ∈ Qcoh(X) admits an F -reflection and thus F is a reflective class in Qcoh(X) (see MacLane (1971) for notation and terminology and Saorín et al (2000) for a nice treatment and characterization of reflective subcategories). So, in particular, we deduce that F is enveloping.…”
Section: Locally Torsion-free Quasi-coherent Sheavesmentioning
confidence: 99%
“…In the previous Corollary 3.7 we showed that the class F of locally torsion-free quasi-coherent sheaves is the right part of a torsion theory in Qcoh(X). One immediate consecuence of this is that each M ∈ Qcoh(X) admits an F -reflection and thus F is a reflective class in Qcoh(X) (see MacLane (1971) for notation and terminology and Saorín et al (2000) for a nice treatment and characterization of reflective subcategories). So, in particular, we deduce that F is enveloping.…”
Section: Locally Torsion-free Quasi-coherent Sheavesmentioning
confidence: 99%
“…The equivalence of (1) and (6) in Corollary 3.10 has been proven in [15,18] using different methods (see [ …”
Section: Global Dimension and Left Derived Functors Of Hommentioning
confidence: 99%
“…closed under extensions, direct summands and taking cones. On the other hand, it is an immediate consequence of the dual of [30,Theorem 3.1] that if C is cocomplete abelian, a subcategory B is coreflective if, and only if, it is precovering and closed under taking cokernels.…”
Section: Introductionmentioning
confidence: 99%